2000
DOI: 10.1002/(sici)1096-8644(200005)112:1<29::aid-ajpa4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of contemporary levels and temporal trends in inbreeding in the Tangier Island, Virginia, population using pedigree data and isonymy

Abstract: In this study we describe inbreeding in a large pedigree from Tangier Island, Virginia, in which we compare two commonly used methods to estimate inbreeding in humans: pedigree and isonymy (identical surnames of spouses). Genealogical data on 3,512 individuals dating back to 1722 were used. Using the pedigree method, we determined an average inbreeding coefficient (F) of 0.00873 for the community as a whole, and 0.018 for inbred individuals. Analysis of temporal trends showed that inbreeding began around 1800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This has been demonstrated in other isolated populations, such as the Hutterites, Finish, and Amish, for multiple complex disorders like bipolar disease, allergic asthma, and familial combined hyperlipidemia, among others ( 39 ). Although the Tangier Island population is isolated and inbred, our previous work has demonstrated that inbreeding levels are refl ective of an avoidance of close consanguinity ( 26 ), rendering Tangier Island generalizable to other European-ancestry populations as refl ected in similar LD patterns and allele frequencies to publicly available databases ( Fig. 2 ; R. A. Mathias, unpublished observations).…”
Section: ) With Thementioning
confidence: 78%
See 2 more Smart Citations
“…This has been demonstrated in other isolated populations, such as the Hutterites, Finish, and Amish, for multiple complex disorders like bipolar disease, allergic asthma, and familial combined hyperlipidemia, among others ( 39 ). Although the Tangier Island population is isolated and inbred, our previous work has demonstrated that inbreeding levels are refl ective of an avoidance of close consanguinity ( 26 ), rendering Tangier Island generalizable to other European-ancestry populations as refl ected in similar LD patterns and allele frequencies to publicly available databases ( Fig. 2 ; R. A. Mathias, unpublished observations).…”
Section: ) With Thementioning
confidence: 78%
“…At the time of subject recruitment (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001), the population was composed of approximately 650 individuals, and the isolated nature of the island has led to sustained low levels of inbreeding ( 26 ). Briefl y, the average inbreeding coeffi cient (F) for the entire Tangier Island population (dating back to 1722) is 0.009 (range, 0.000-0.156; n = 3,512).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surnames have proved to be useful for describing the population structure, and isonymy makes it possible to evaluate isolation and consanguinity (see the recent bibliography in Barrai et al, 13 Mathias et al, 14 RodriguezLarralde, 15 Lasker et al, 16 Sykes et al, 17 Manni et al, 18 Barrai et al, 19,20 Caravello et al, 21 Gagnon et al, 22 ). They are also frequently used as a tool to identify individuals' geographical origin (see the recent bibliography in Chan, 23 GarzaChapa et al, 24 De Silvesti and Guglielmino, 25 Pollock et al, 26 Jacobs and Landerdale, 27 Rudan, 28 Carta et al, 29 Brancatelli et al 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…While such isolates exist, including the Hutterite communities (Steinberg AG 1967), Old Order Amish communities (Agarwala et al 2003), and residents of Tangier Island (Mathias et al 2000), the relatively short time since initial immigration, the high mobility of citizens, and the paucity of distant historical and genealogical records make the identification of new population isolates difficult.…”
mentioning
confidence: 99%